The mechanisms of specialized pro-resolving mediators in pain relief: neuro-immune and neuroglial regulations - Chen, Yushan; Wu, Xuewei; Li, Jiaqi; Ren, Yuxuan; Miao, He; Zhai, Xiaojie; Huang, Changshun; Chen, Xiaowei (Frontiers in Immunology, 2025)
Chronic pain remains a significant global health challenge. Current anti-nociceptive therapies often fail to provide adequate relief and are associated with adverse side effects, underscoring the need for novel therapeutic approaches. Specialized pro-resolving mediators (SPMs)—bioactive lipid compounds derived from omega-3 and omega-6 fatty acids—have recently garnered attention as potential agents for pain management due to their dual anti-inflammatory and inflammation-resolving properties. This review explores the multifaceted anti-nociceptive effects of SPMs, focusing on their mechanisms of action in diverse pain models, including neuropathic, inflammatory, cancer-induced, postoperative, and spontaneous pain. We highlight the distinct roles of specific SPMs, such as Resolvin D1 (RvD1), Resolvin E1 (RvE1), and Maresin 1 (MaR1), in modulating pain pathways through mechanisms such as suppression of inflammatory cytokines, modulation of transient receptor potential (TRP) channels, and interactions with immune cells to resolve inflammation. Additionally, we discuss the implications of sexual dimorphism in SPM efficacy, endogenous SPM biosynthesis, and therapeutic strategies involving omega-3 fatty acid supplementation. While preclinical studies demonstrate the therapeutic promise of SPMs, critical gaps persist in understanding their precise mechanisms, long-term safety, and translational potential. This review emphasizes the need for rigorous preclinical and clinical research to elucidate SPMs’ role in managing recalcitrant pain conditions, with the aim of advancing targeted, non-opioid pain therapies.